Teachers' Strategies in Teaching English Vocabulary to Young Learners: A Case Study in an Elementary School in South Sumatera, Indonesia - Riznanda, Winny Agustia (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2023)
One of the essential components in education are teachers’ strategies. Thus, the aim of this study was to investigate strategies utilized by teachers of SD YKPP Pendopo, PALI, South Sumatera in teaching English vocabulary. Case study, one of the qualitative research designs, was applied for this study. Purposeful sampling was applied in determining the participants. Thus, two teachers with degrees on English Education and acquire more than five years of experience in teaching English to young learners were selected. Open-ended questions in a semi-structured interview and observation were applied to obtain the data. Then, thematic analysis was employed to analyze the data. This study resulted that the teachers applied Realia Strategy, Visual Scaffolding Strategy, Modeled Talk Strategy, Collecting Word Strategy, Vocabulary Role-Play Strategy, and Leveled Question Strategy, and Sing a Song Strategy. This study implies that teachers are suggested to apply appropriate strategies in teaching to embrace the students’ distinctiveness.